1997
DOI: 10.2514/2.68
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation of Low Reynolds Number Flows in Symmetric Channels

Abstract: The ow elds in two-dimensional channels with discontinuous expansions are studied numerically to understand how the channel expansion ratio in uences the symmetric and non-symmetric solutions that are known to occur. For improved con dence and understanding, two distinct numerical techniques are used. The general ow eld characteristics in both symmetric and asymmetric regimes are ascertained by a time-marching nite volume procedure. The ow elds and the bifurcation structure of the steady solutions of the Navie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(40 citation statements)
references
References 15 publications
5
34
0
Order By: Relevance
“…II, ER = 3, which is similar to what is done in the literature for the same flow (see, for instance, Hawa and Rusak 7 and Battaglia et al 5 ). A mesh composed of triangular elements is generated though the Delaunay-Voronoi algorithm.…”
Section: A Base Flowsupporting
confidence: 84%
See 4 more Smart Citations
“…II, ER = 3, which is similar to what is done in the literature for the same flow (see, for instance, Hawa and Rusak 7 and Battaglia et al 5 ). A mesh composed of triangular elements is generated though the Delaunay-Voronoi algorithm.…”
Section: A Base Flowsupporting
confidence: 84%
“…3 of the flow configuration, the two reattachment points differ as reported in the figure. Data from Alleborn et al 8 and Battaglia et al 5 are also shown, in order to validate the present results. An overall very good agreement is observed.…”
Section: B Stability Analysissupporting
confidence: 71%
See 3 more Smart Citations